Identification and Characterization of Inhibitors of Bacterial Enoyl-Acyl Carrier Protein Reductase - Ling, Losee L. (American Society for Microbiology, 2004)
Bacterial enoyl-acyl carrier protein reductase (ENR) catalyzes an essential step in fatty acid biosynthesis. ENR is an attractive target for narrow-spectrum antibacterial drug discovery because of its essential role in metabolism and its sequence conservation across many bacterial species. In addition, the bacterial ENR sequence and structural organization are distinctly different from those of mammalian fatty acid biosynthesis enzymes. High-throughput screening to identify inhibitors of Escherichia coli ENR yielded four structurally distinct classes of hits. Several members of one of these, the 2-(alkylthio)-4,6-diphenylpyridine-3-carbonitriles (“thiopyridines”), inhibited both purified ENR (50% inhibitory concentration [IC(50)] = 3 to 25 μM) and the growth of Staphylococcus aureus and Bacillus subtilis (MIC = 1 to 64 μg/ml). The effect on cell growth is due in part to inhibition of fatty acid biosynthesis as judged by inhibition of incorporation of [(14)C]acetate into fatty acids and by the increased sensitivity of cells that underexpress an ENR-encoding gene (four- to eightfold MIC shift). Synthesis of a variety of compounds in this chemical series revealed a correlation between IC(50) and MIC, and the results provided initial structure-activity relationships. Preliminary structure-activity relationships, potency on purified ENR, and activity on bacterial cells indicate that members of the thiopyridine chemical series are effective fatty acid biosynthesis inhibitors suitable for further antibacterial development.